Asbestos awareness among the residents of St. Kitts and Nevis: a cross-sectional study - Denrick Jeffers; Yu-Chi Liao; Ken Takahashi; Ro-Ting Lin (BMC, 2022)
Abstract Background High levels of public awareness regarding the hazards of asbestos, rights to health, and benefits of an asbestos-free country can increase advocacy and political commitment to a total ban on asbestos. We aimed to investigate asbestos awareness and associated sociodemographic characteristics among the adult population of St. Kitts and Nevis. Methods In this cross-sectional study, 1009 participants completed an online questionnaire with questions about sociodemographic data and asbestos awareness. We applied multiple regression models to estimate associations between sociodemographic factors, levels of asbestos knowledge, and attitudes toward asbestos management. Results We found that 70% of residents of St. Kitts and Nevis considered asbestos exposure to be a general public concern and believed the government should prevent it. Of all participants, 54% were in favor of completely banning the use and importation of all asbestos products and materials; those with higher levels of asbestos knowledge were more likely to favor a total ban. Higher proportions and odds of favoring a total asbestos ban were also observed in participants aged ≥ 30 years, women, those with higher education, and those living in St. Kitts (vs. Nevis). Conclusions These findings support implementing policies to regulate and outright ban the use of asbestos products and materials in St. Kitts and Nevis. This data can be used to develop tailored campaigns to improve asbestos knowledge among sociodemographic groups with lower asbestos awareness, such as in the wider Caribbean and other under-resourced countries.